KAJIAN STRUKTUR TEKS, BENTUK KATA DAN JENIS QÄ€FIYAH ATAS QASHÄªDAH HUWA AN-NÅªR KARYA HABIB ALI AL-HABSYI - Umam, Muhammad Asroful; Farhah, Eva (Balai Bahasa Jawa Timur, 2018)
ABSTRACTThis researchgoals to describe the text structure of Qash?dah Huwa an-N?r based on Badr's structural theory and explain the form of the word and type of q?fiyah used. The method used is qualitative descriptive with technique of analysis in the form of library technique. The results of this research include text structure as Jawwun-Nash, Al-?Ardhu Al-??m Li an-Nashshi, al-Fikrah, ?Awatif, and language styles. The feature of using figure of speech metaphor and hyperbola is expressed in simple words. Based on the research of the form of words and types of q?fiyah, Qash?dah Huwa an-N?r has two types of words, that is some words and one word.While the type q?fiyah include; The variety of q?fiyah is muthlaqah. The alphabetsof q?fiyah are rawiyy muthlaq washl, khur?j, ta's?s, and dakh?l. The Vowels of q?fiyah are rass, majr?, isyb?' and Naf?dz. The name of q?fiyah is a mutad?rik and disablement of q?fiyah is not found in this qash?dah.